PENGARUH INTELLECTUAL CAPITALDAN FIRM SIZETERHADAP PROFITABILITAS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA: Studi Empiris Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2016-2018 (STIE Rajawali Purworejo, 2021)
This research aims to determine the influence of Intellectual Capital consisting of Value Added Capital Employed (VACA), Value Added Human Capital (VAHU) and Structural Capital Value Added (STVA) and Firm Size on manufacturing companies listed on the BEI for the 2016 – 2018 period. This research uses a population of manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the period 2016 – 2018. This research uses secondary data as research material and a purposive sampling method to determine the sample to be used and produces a final sample of 162 manufacturing companies. After carrying out the sampling criteria, 8 companies were used as samples. The data in this study were analyzed using the SPSS program. The analysis used is descriptive analysis, classical assumption testing, statistical analysis and hypothesis testing. The results of this research show that Value Added Capital Employed (VACA), Value Added Human Capital (VAHU) and Structural Capital Value Added (STVA) have a positive influence on profitability. Meanwhile, firm size shows different results. Firm size has no effect on profitability.